2021
DOI: 10.1029/2020jb019573
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Igneous Layering in the Lower Oceanic Crust From the Samail Ophiolite, Sultanate of Oman

Abstract:  Gravitational sorting in density currents may be a key process in the formation of dmscale modal layers.  Cyclical nucleation and growth of large crystals at the expense of smaller ones can create mm-scale olivine-rich bands.  Shear strain can create and emphasize primary modal layering in cumulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 121 publications
(190 reference statements)
10
23
0
Order By: Relevance
“…The observed features are very similar to those in the layered gabbros described by Mock et al. (2020) in Wadi Somerah (Sumail block); they suggested as a formation mechanism that the layers were deposited by density currents of crystal‐laden magma within a sill environment. Much more abundant within the Layered Gabbro Unit are gabbros showing cryptic layering, where the establishment of a stratiform layering is not visible.…”
Section: Resultssupporting
confidence: 84%
“…The observed features are very similar to those in the layered gabbros described by Mock et al. (2020) in Wadi Somerah (Sumail block); they suggested as a formation mechanism that the layers were deposited by density currents of crystal‐laden magma within a sill environment. Much more abundant within the Layered Gabbro Unit are gabbros showing cryptic layering, where the establishment of a stratiform layering is not visible.…”
Section: Resultssupporting
confidence: 84%
“…(2004) and supported by Mock et al. (2021). “Full Sheeted Sills' model is proposed in this study, melts derived directly from the mantle are shown in red; orange‐yellow regions correspond to mixtures of primitive melts and evolved melt emplaced in the upper gabbros after fractional crystallization in the lower gabbros.…”
Section: Discussionsupporting
confidence: 55%
“…Mock et al. (2021) argued for a Hybrid‐style model similar to Maclennan et al. (2004) and Kelemen et al.…”
Section: Discussionmentioning
confidence: 77%
“…They determined fast and near uniform cooling rates with depth (∼1-10 −2 °C/y), and inferred that hydrothermal circulation cooled the entire Hess Deep lithosphere, which accreted from solidification of periodically replenished magma bodies (sills). Mock et al (2021) investigated gabbros from the mid-plutonic and lowermost crust at the southern Oman ophiolite (Samail and Wadi Tayin massifs, respectively), recovering cooling rates of ∼10 −2 °C/y and ∼10 −1 °C/y through Ca-in-olivine and Mg-in-plagioclase closure temperatures, and demonstrating efficient heat loss from the lowermost crust, perhaps by deep hydrothermal circulation.…”
Section: Results From Previous Investigations That Constrained Cooling Rate Variations In Oceanic Lithospherementioning
confidence: 99%